PEMBERIAN ARANG AKTIF, ZEOLIT, DAN MANGANESE GREENSAND TERHADAP SURVIVAL Oreochromis niloticus PADA SISTEM TRANSPORTASI - Mahendra Mahendra; Fazril Saputra; Citra Dina Febrina; Yusran Ibrahim; Farah Diana; Sufal Diansyah (JURNAL PERIKANAN TROPIS, 2020)
This study aims to determine the effect of administration of activated charcoal, zeolite, and manganese greensand on survival Oreochromis niloticus. The experimental design used was a completely randomized design (CRD) with 4 treatments and 3 repetitions. The treatments are P1 = without administration (control), P2 = administration of activated charcoal 10 gr/l P3 = administration of Zeolite 10 gr/l and P4 = administration of manganese 10 gr/l. The parameter observed in this study was survival Oreochromis niloticus. The results showed that administration of activated charcoal, zeolites, and manganese greensand significantly affected the survival of Oreochromis niloticus. The best value is obtained at treatment P1; P2; and P3, each with the best average survival value of 96%; 91%; and 91%. The lowest cost incurred is the treatment P1 Rp. 66.200, - with SR 96% transportation.